Pengaruh Pemberian Terapi Musik Dan Back Exerciseterhadap Penurunan Tingkat Nyeri Dysmenorrhea Primer - Astutik, Yuyun; , Dwi Kurniawati, SSt.FT; , Wahyuni, SSt.FT.M.Kes (2015)
Background: Dysmenorrhea / menstruation painful is a painful around and during menstruation, sometimes bringing on activity nuisance and need a rest. The pain commonly felt is a cramps which rise and sink or painful which continuous ordinarily in the lower abdomen which spread until the lower back. These menstruation pains appear because distrimikmiometerium which indicate one or more phenomenon which started from lower until highest pain. The dysmenorrhea primer is menstruation pain that happened without any real deviation gynecologic. One of exercise which gave for dysmenorrhea primer is back exercise and music therapy. Objective: to find out the music and back exercise therapy giving for decreasing level pain dysmenorrhea primer. Methods of study: This research is Quasi experimental pre and posttest with control group design research. The subject in this research is female university student which dweller GriyaDara boarding house. The amount of sample in this research is 30 samples. The statistic test will be used in Paired Sample T-test and Independent Sample T-test. The Result: the influence test use Paired Sample T-test for experiment group show the result p = 0,0001 < 0,05 and in control group p = 0,001 < 0,05 the different influence test between experiment and control group use Independent Sample T-test show significant result 0,017 which mean there are influence differences between experiment and control group. Conclusion: Giving music and back exercise therapy is influential for decreasing pain level of dysmenorrhea primer.